Patients with chronic Achilles tendon rupture have persistent limitations in patient‐reported function and calf muscle function one year after surgical treatment – a case series - Anna Nordenholm; Niklas Nilsson; Eric Hamrin Senorski; Katarina Nilsson Helander; Olof Westin; Nicklas Olsson (Journal of Experimental Orthopaedics, 2022)
Abstract Purpose Evaluate the one‐year postoperative outcomes in patients with Chronic Achilles tendon rupture. Methods Patients surgically treated for Chronic Achilles tendon rupture (n = 22, 14 males and 8 females, mean age 61 ± 15) were evaluated by Achilles tendon Total Rupture Score, The Physical Activity Scale, The Foot and Ankle Outcome Score, Calf muscle endurance test, counter movement jump, Hopping, ultrasound measurement of tendon length, Achilles Tendon Resting Angle, dorsi flexion range of motion and calf muscle circumference. Muscle function and tendon length outcomes on the injured side were compared with the healthy side. Results The patients scored a mean of 62 ± 26 on the Achilles tendon Total Rupture Score. Median scores on the injured compared with the healthy side were lower in heel‐rise repetitions (20 vs 24 cm, p = 0.004), hel‐rise height (8 vs 10 cm, p < 0.001), heel‐rise total work (872 vs 1590 joule, p < 0.001) and hopping ratio (0.37 vs 0.48, p = 0.005). Median calf circumference was smaller (37 vs 38 cm, p = 0.001) and the mean tendon elongation greater on the injured side; Achilles tendon resting angle (55 vs 50°, p < 0.001) and ultrasound (22.4 vs 20.5 cm, p = 0.006). Conclusions At one year postoperatively, patients with chronic Achilles tendon rupture reported persistent limitations in subjective foot and ankle function. Heel‐rise height and total work as well as hopping ratio were not recovered, and there was an elongation of the injured Achilles tendon compared with the healthy tendon. Level of evidence IV